2010
DOI: 10.3138/cmlr.66.5.711
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of L2 Dialect on Learning French Vowels: Native English Speakers Learning Québécois and European French

Abstract: This article examines how a second language (L2) dialect affects how accurately the L2 is perceived and produced. Specifically, the study examined differences between the production and perception of French vowels /i/, /y/, and /u/ by learners of either Québec French (QF) or European French (EF). These vowels differ across the two varieties, both acoustically and because of assibilation of /t-d/ before /i-y/ for QF versus EF. As a result of these differences, QF has an additional acoustic cue with which to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 35 publications
2
24
1
Order By: Relevance
“…For instance, Escudero and Boersma (2004) showed that Spanish learners of Scottish English will, at the beginning of their L2 development, have more difficulty perceiving the /i+-I/ contrast than Spanish learners of Southern British English because these two vowels are not contrasted by duration in Scottish English. Baker and Smith (2010) showed that English learners of Québéc French differ from English learners of European French in how accurately they can discriminate the French /i-y-u/ contrast. Importantly, while learners of different L2 varieties have some different perceptual assimilation patterns, it is also likely that the specific dialect of the listener's L1 may affect foreign-language or L2 perception.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Escudero and Boersma (2004) showed that Spanish learners of Scottish English will, at the beginning of their L2 development, have more difficulty perceiving the /i+-I/ contrast than Spanish learners of Southern British English because these two vowels are not contrasted by duration in Scottish English. Baker and Smith (2010) showed that English learners of Québéc French differ from English learners of European French in how accurately they can discriminate the French /i-y-u/ contrast. Importantly, while learners of different L2 varieties have some different perceptual assimilation patterns, it is also likely that the specific dialect of the listener's L1 may affect foreign-language or L2 perception.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, QF /yː/ and /uː/ vowels are also more separated acoustically in the vowel space than are EF vowels. Two features of the Baker and Smith (2010) study, however, cause the findings to be unclear: In the Baker and Smith (2010) study, it was unclear whether the additional acoustic cue or greater separation in the vowel space influenced Québécois French learners' ability to more accurately produce and perceive French vowels. Similarly, it was also unknown whether exposure to two dialects influenced the QF learners' greater accuracy than that of EF learners, since the QF learners were exposed to both European and Québécois French (unlike the EF learners who were only exposed to European French).…”
Section: Introductionmentioning
confidence: 87%
“…The effect of the L2 dialect on L2 phonological learning seems especially salient if one dialect contains acoustic cues that help in distinguishing between difficult L2 sound contrasts. Baker and Smith (2010), for example, found that learners of Québécois French (QF) were Brought to you by | HEC Bibliotheque Maryriam ET J. Authenticated Download Date | 6/26/15 4:21 AM more accurate than learners of European French (EF) at perceiving and producing French /iː/, /yː/, and /uː/. QF learners' increased accuracy may have been caused by two factors: QF has an extra acoustic cue (assibilation of alveolar consonants before high front vowels) that distinguishes between French /yː/-/uː/.…”
Section: Introductionmentioning
confidence: 97%
“…This is an ideal target phoneme for pronunciation instruction because, as mentioned earlier, /y/ is highly problematic for speakers of a variety of first languages (e.g. English, Mandarin, Spanish) in both production and perception (Baker and Smith, 2010;Levy and Strange, 2008). According to Flege's (1995) Speech Learning Model, during acquisition, speech perception becomes attuned to the contrastive phonic elements of the L1 and thus learners may fail to discern the phonetic differences between sounds in the L2.…”
Section: French /Y/ and Its Acquisitionmentioning
confidence: 99%
“…In the investigation, we focus on the acquisition of the French phoneme /y/ (as in tu /ty/ 'you') for two main reasons: (1) the sound is highly difficult to acquire in both production and perception (e.g. Baker and Smith, 2010;Levy and Law II, 2010;Rochet, 1995); and (2) it has a high functional load in the target language (Jenkins, 2002;King, 1967), as it is used to distinguish many French minimal pairs such as au-dessous /od.su/ 'below' and au-dessus /od.sy/ 'above'. To our knowledge, there are no studies that have investigated the use of ASR on mobile devices for pronunciation teaching (see also Godwin-Jones, 2009, for a similar observation).…”
Section: Introductionmentioning
confidence: 99%